Transcatheter valve-in-ring and para-ring vascular plug implantation for severe tricuspid regurgitation following annuloplasty ring failure: a case report. Issue 2 (1st February 2022) - Sharma, Harish; Nadir, M Adnan; Steeds, Richard P; Doshi, Sagar N
Abstract: Background: Moderate or severe tricuspid regurgitation (TR) recurs in up to one-third of patients within 8 years of surgical annuloplasty repair. Reoperation often carries high risk with poor outcomes. Transcatheter valve-in-ring repair is an emerging alternative treatment. However, residual regurgitation is frequent and may necessitate further procedures. Case summary: A 52-year-old female was diagnosed with severe rheumatic valvular heart disease. The patient underwent mechanical aortic and mitral valve replacement. Additionally, tricuspid repair was performed using a semi-rigid annuloplasty ring (28 mm Edwards Physio Tricuspid). Within 2 years, the patient developed recurrent, isolated severe symptomatic TR, with progressive right ventricular dilatation. The patient was considered prohibitive risk for redo surgery and unsuitable for cardiac transplantation. She underwent percutaneous valve-in-ring transcatheter heart valve (THV) implantation using a 29 mm Sapien S3 (Edwards Lifesciences, CA, USA) valve. Persistent severe residual para-ring TR warranted a further procedure to deploy vascular plugs, significantly reducing the TR to a mild jet with symptomatic improvement. Discussion: Valve-in-ring THV implantation for failed surgical tricuspid annuloplasty repair is a rare procedure reserved for symptomatic patients at high or prohibitive risk for reoperation. Significant residual TR is a commonly encountered problem with incomplete annuloplasty rings following valve-in-ring procedures and may occur either intra-ring between the THV and the ring or para-ring. Implantation of vascular occlusion devices can be used to successfully treat residual TR at either location with good outcomes at 6-month follow-up. Further work is required to determine the longevity of this treatment.